PERAN KOMITMEN AFEKTIF DALAM MEMEDIASI GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KARAKTERISTIK PEKERJAAN TERHADAP KINERJA KARYAWAN IKM KONVEKSI - Rifdah Abadiyah; Ilviyah, Lailatul (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2022)
This study aims to determine the effect of transformational leadership style on employee performance, to determine the effect of job characteristics on employee performance, to determine the effect of affective commitment on employee performance, to determine the effect of transformational leadership style on affective commitment, to determine the effect of job characteristics on affective commitment, to determine the effect of transformational leadership style on employee performance through affective commitment as an intervening variable, to determine the effect of job characteristics on employee performance through affective commitment as an intervening variable at IKM Ridzil Jaya Utama. This research is a quantitative type of research. The source of data in this study is primary data obtained through questionnaires. The research subjects used were all production employees of IKM Ridzil Jaya Utama, totaling 60 employees. Test the validity of the data in this study using Path Analysis, Hypothesis Testing. The results of the study concluded that transformational leadership style affects employee performance. Job characteristics affect employee performance. Affective commitment does not affect employee performance. Transformational leadership style affects affective commitment. Job characteristics do not affect affective commitment. Transformational leadership style has no effect on employee performance through affective commitment as an intervening variable. Job characteristics have no effect on employee performance through affective commitment as an intervening variable at IKM Ridzil Jaya Utama.